2020
DOI: 10.1177/0145561320977464
|View full text |Cite
|
Sign up to set email alerts
|

Taste and Smell Impairment in Critically Ill Patients With COVID-19: An Intensive Care Unit Study

Abstract: Objective: To determine taste and smell impairment rates in patients with coronavirus disease 2019 (COVID-19) who were hospitalized in the intensive care unit (ICU). Methods: Between March 2020 and May 2020, patients with COVID-19 hospitalized in the ICU were enrolled in this study. Upon discharge, patients were telephoned and asked to complete a survey related to taste and smell impairment. Characteristics were compared between patients with and without taste and/or smell impairment. Results: Fifty-two patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 18 publications
1
10
1
2
Order By: Relevance
“…The prevalence of OD±GD in our studied population was 12.8%. This is considerably lower than that of surveys conducted in hospitalised patients in Europe (35.0%–80.6% for OD and 21.0%–90.3% for GD within 1 month),25–27 and in other countries such as Turkey (42.3% for OD±GD),28 and Brazil (64.6% and 66.7% for OD and GD, respectively, at follow-up of 15–55 days) 29. The longer follow-up at which our study has been conducted could explain the lower rate of observed chemosensory alteration in our population, whereby recovery of OD/GD is expected to happen over time in some patients.…”
Section: Discussionmentioning
confidence: 60%
“…The prevalence of OD±GD in our studied population was 12.8%. This is considerably lower than that of surveys conducted in hospitalised patients in Europe (35.0%–80.6% for OD and 21.0%–90.3% for GD within 1 month),25–27 and in other countries such as Turkey (42.3% for OD±GD),28 and Brazil (64.6% and 66.7% for OD and GD, respectively, at follow-up of 15–55 days) 29. The longer follow-up at which our study has been conducted could explain the lower rate of observed chemosensory alteration in our population, whereby recovery of OD/GD is expected to happen over time in some patients.…”
Section: Discussionmentioning
confidence: 60%
“…Murat et al, 2020;Nakagawa et al, 2020Nakagawa et al, , 2020Nakakubo et al, 2020;Nakanishi et al, 2020;Noh et al, 2020;Otte et al, 2020;Ozcelik Korkmaz et al, 2020;Paderno et al, 2020;Patel et al, 2020;Perlman et al, 2020;Petersen et al, 2020;Petrocelli et al, 2020bPetrocelli et al, , 2020aPinna et al, 2020;Printza et al, 2020Printza et al, , 2021Qiu et al, 2020;Rajkumar et al, 2020;Ramteke et al, 2020Ramteke et al, , 2020Rojas-Lechuga et al, 2020;Roland et al, 2020;Romero-Sanchez et al, 2020; Rubel et al, 2020;Sakalli et al, 2020;Salepci et al, 2020;Sayin et al, 2020aSayin et al, , 2020bSchirinzi et al, 2020;Schmithausen et al, 2020;Seo et al, 2020;Shoer et al, 2020;Sierpinski et al, 2020;Smith et al, 2020;Somekh et al, 2020; Speth et al, 2020;Spinato et al, 2020;Stavem et al, 2020; Sun et al, 2020;Teklu et al, 2020;Tham et al, 2020;Tsivgou...…”
unclassified
“…A total of 2235 articles were screened, scrutinized 109 full-text articles, and ultimately 26 studies met the inclusion criteria for meta-analysis (Figure 1). Those studies documented patients with and without olfactory and gustatory dysfunction(Le Sanli et al, 2021;Rojas-Lechuga et al, 2021;Sayın et al, 2021;Dev et al, 2021;Sheng et al, 2021;Elibol and Baran, 2021;Samimi et al, 2021;Sahoo et al, 2021;Singer-Cornelius et al, 2021;Porta-Etessam et al, 2021;Gupta et al, 2021;Soh et al, 2021;Tabari et al, 2021;Jain et al, 2021;Lee et al, 2021;Cheng et al, 2021;Ahn and Min, 2021;Klopfenstein et al, 2020;Lv et al, 2020;Jalessi et al, 2020;Petrocelli et al, 2020;Prajapati et al, 2020;Shah et al, 2020;Altundag et al, 2020;Tham et al, 2020).The 83 excluded articles and the reasons for exclusion are 6 provided in Table 2 in the Supplement.…”
Section: Resultsmentioning
confidence: 99%